Atto488-Agitoxin 2—A Fluorescent Ligand with Increased Selectivity for Kv1.3 Channel Binding Site - Kristina R. Denisova; Nikita A. Orlov; Sergey A. Yakimov; Mikhail P. Kirpichnikov; Alexey V. Feofanov; Oksana V. Nekrasova (Bioengineering, 2022)
Fluorescently labeled peptide blockers of ion channels are useful probes in studying the localization and functioning of the channels and in the performance of a search for new channel ligands with bioengineering screening systems. Here, we report on the properties of Atto488-agitoxin 2 (A-AgTx2), a derivative of the Kv1 channel blocker agitoxin 2 (AgTx2), which was N-terminally labeled with Atto 488 fluorophore. The interactions of A-AgTx2 with the outer binding sites of the potassium voltage-gated Kv1.x (x = 1, 3, 6) channels were studied using bioengineered hybrid KcsA–Kv1.x (x = 1, 3, 6) channels. In contrast to AgTx2, A-AgTx2 was shown to lose affinity for the Kv1.1 and Kv1.6 binding sites but to preserve it for the Kv1.3 site. Thus, Atto488 introduces two new functionalities to AgTx2: fluorescence and the selective targeting of the Kv1.3 channel, which is known for its pharmacological significance. In the case of A-AgTx2, fluorescent labeling served as an alternative to site-directed mutagenesis in modulating the pharmacological profile of the channel blocker. Although the affinity of A-AgTx2 for the Kv1.3 binding site was decreased as compared to the unlabeled AgTx2, its dissociation constant value was within a low nanomolar range (4.0 nM). The properties of A-AgTx2 allow one to use it for the search and study of Kv1.3 channel blockers as well as to consider it for the imaging of the Kv1.3 channel in cells and tissues.